Using flash games to stimulate cooperative communication - Gabarre, Serge; Gabarre, Cecile (Asia Association of Computer-Assisted Language Learning, 2009)
The benefits of using games in the language class are numerous (Godwin-Jones, 2005). Playing computer games have become a popular form of relaxation for many learners (Yang, 2001). Can this phenomenon be utilized to support foreign language teaching at the tertiary level? In this research, a group of 15 Malaysian students were asked to solve a puzzle in a Flash game. Their task was simple: exit from a virtual room without a door. The computer/language lab used for this task was the Sanako Lab 300. Each learner had access to a single computer as well as a microphone and a headphone. The class had been divided into three groups of four students each and one group of three. In order to create an information gap task, four different audio instructions were available to each group. Each member of a group was required to communicate with the other three groups in order to complete the task